2015
DOI: 10.3171/2015.1.jns141811
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy in patients with nonlesional MRI and normal memory: an SEEG study

Abstract: OBJECT Temporal lobe epilepsy (TLE) in the absence of MRI abnormalities and memory deficits is often presumed to have an extramesial or even extratemporal source. In this paper the authors report the results of a comprehensive stereoelectroencephalography (SEEG) analysis in patients with TLE with normal MRI images and memory scores. METHODS Eighteen patients with medically refractory epilepsy who also had unremarkable MR images and normal verbal and visual memory scores on neuropsychological testing were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…There were 12 studies that reported on epilepsy duration, with no significant difference between SEEG patients (mean = 126.8 months ± 65.0, median = 121.8) and SDE patients (mean = 62.4 months ± 51.1, median = 51.4; Table ). Among the SEEG patients, the etiology was identified as a temporal epileptogenic focus in 42.2% of patients, tumor in 6.7% of patients, FCD1 in 39.2% of patients, FCD2 in 10.7% of patients, and lesional in 41.5% of patients .…”
Section: Resultsmentioning
confidence: 99%
“…There were 12 studies that reported on epilepsy duration, with no significant difference between SEEG patients (mean = 126.8 months ± 65.0, median = 121.8) and SDE patients (mean = 62.4 months ± 51.1, median = 51.4; Table ). Among the SEEG patients, the etiology was identified as a temporal epileptogenic focus in 42.2% of patients, tumor in 6.7% of patients, FCD1 in 39.2% of patients, FCD2 in 10.7% of patients, and lesional in 41.5% of patients .…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation might be that patients with TLE and N-MRI constitute a very heterogeneous group. In fact, some of them may be truly non-lesional (N-HP), while others may have different histopathological findings as demonstrated in several studies [14, 22, 29, 33, 34]. Due to different ratios of histopathological substrates in each study, the seizure outcomes between various reports are difficult to compare.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior temporal lobectomy (ATL) and amygdalohippocampectomy (SAH) are commonly used among these centers; neocortectomy was also used for lateral TLE [15,17], especially for dominant temporal lobe [15]; multiple hippocampal transection was applied for mesial TLE in a report from Cleveland [22]. Seizure outcome after surgery was not significantly different between an independent mesial and lateral epileptic focus among patients with MRI-negative TLE (61.3% vs. 53.3%, OR = 1.39, 95% CI = 0.61-3.20, p = 0.43, I 2 = 8%) (Fig.…”
Section: Independent Mesial Vs Lateral Temporal Lobe Epileptic Focusmentioning
confidence: 99%
“…Several studies have attempted to identify the prognostic factors for seizure-free outcome after surgery in MRI-negative TLE patients, including age, epilepsy duration, pathology, and fluorodeoxyglucose positron emission tomography (FDG-PET), single photon emission computer tomography (SPECT), scalp electroencephalogram (EEG), and intraoperative EEG results [2,5,[7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, further investigation is required due to the shortage of cases and the inconsistent and occasionally contradictory findings.…”
Section: Introductionmentioning
confidence: 99%